Identification of a Candidate Gene for Panicle Length in Rice (Oryza sativa L.) Via Association and Linkage Analysis - Liu, Erbao; Liu, Yang; Wu, Guocan; Zeng, Siyuan; Tran Thi, Thu G.; Liang, Lijun; Liang, Yinfeng; Dong, Zhiyao; She, Dong; Wang, Hui; Zaid, Imdad U.; Hong, Delin (Frontiers in Plant Science, 2016)
Panicle length (PL) is an important trait for improving panicle architecture and grain yield in rice (Oryza sativa L.). Three populations were used to identify QTLs and candidate genes associated with PL. Four QTLs for PL were detected on chromosomes 4, 6 and 9 through linkage mapping in the recombinant inbred line population derived from a cross between the cultivars Xiushui79 (short panicle) and C-bao (long panicle). Ten SSR markers associated with PL were detected on chromosomes 2, 3, 5, 6, 8, 9 and 10 in the natural population consisting of 540 accessions collected from East and Southeast Asia. A major locus on chromosome 9 with the largest effect was identified via both linkage and association mapping. LONG PANICLE 1 (LP1) locus was delimited to a 90-kb region of the long arm of chromosome 9 through fine mapping using a single segment segregating F2 population. Two single nucleotide polymorphisms (SNPs) leading to amino acid changes were detected in the third and fifth exons of LP1. LP1encodes a Remorin_C-containing protein of unknown function with homologs in a variety of species. Sequencing analysis of LP1 in two parents and 103 rice accessions indicated that SNP1 is associated with panicle length. The LP1 allele of Xiushui79 leads to reduced panicle length, whereas the allele of C-bao relieves the suppression of panicle length. LP1 and the elite alleles can be used to improve panicle length in rice.